A soil loosening machine for winter earth‐moving in transport construction - Dyakov, Ivan; Ivkin, Valeriy; Popovich, Alexey (Transport, 2007)
The main methods of frozen soil loosening are considered from the perspective of their effectiveness in transport‐related construction, and a new type of equipment is offered for earth‐moving in winter conditions.First Published Online: 27 Oct 2010